Exploring the Structure, Function and Stability of Glutathione Transferases Engineered from Intra- and Inter-class Consensus Sequences: How Forgiving is Nature? - Mulenga, Thabelo (University of the Witwatersrand, Johannesburg, 2024)
Protein folding is an enigmatic biochemical process that is foundational to the structural and functional requirements of a cell. The problem of protein folding, in a nutshell, concerns itself with the rate of protein folding as well as the conversion of amino acids from a linear sequence to a fully folded structure. This problem is partly answered by the existence of folding pathways. The folding funnel was conceptualised as a depiction of folding pathways, and it is a framework that illustrates that native proteins naturally favour the lowest energy state, encountering kinetic and thermodynamic barriers as they fold. Consensus protein design, based on this understanding, aims to: (1) enhance stability and (2) navigate the pitfalls of folding by modifying the folding funnel of a protein. This approach can also shed light on the significance of evolutionarily conserved residues. In this study, consensus protein mutants were generated for the Alpha and Mu glutathione transferases (GSTs) classes. The consensus proteins were then benchmarked against the parental proteins that were chosen (hGSTA1-1 and hGSTM1-1). The Alpha consensus mutant had 11 consensus mutations, including a notable M50L mutation, which affects the dynamic behaviour of helices α2 and α9, while the Mu consensus mutant had 13 unique mutations. Protein production and purification showed that the Mu consensus mutant had larger and purer yields. Data from far-UV circular dichroism studies and root-mean-squared-fluctuation (RMSF) from molecular dynamics (MD) simulations showed that the secondary structural components of the Alpha and Mu proteins remained largely the same, although the Alpha consensus mutant displayed a far lower molar residue ellipticity reading than its wildtype counterpart, indicating the disruption of secondary structural elements, likely caused by the M50L mutation. The ANS binding results showed that the M50L mutation in the Alpha consensus protein caused an increase in exposure of the surface area of the H-site, while the Mu consensus protein had a decrease in the solvent accessibility of its H-site. Thermal shift assay results indicated the consensus proteins had increased thermal stability. Enzyme kinetics results showed that the functionality of the proteins was severely diminished in the consensus mutants, particularly the Alpha consensus mutant. MD simulation results showed that there was an overall increase in the rigidity and compactness of the consensus mutant proteins, further affirming the improvement of thermal stability, while signalling the loss in functionality. The results produced herein have the potential to facilitate the proliferation of engineered GSTs for biotechnological applications that require proteins with an increased half-life and greater stability.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science, to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Glutathione transferase; Consensus protein design; Protein structure; Protein function; Protein stability; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-15: Life on land